Harnessing diversity from ecosystems to crops to genes - Buchanan-Wollaston, Vicky; Wilson, Zoe A.; Tardieu, François; Beynon, Jim; Denby, Katherine (Wiley Open Access, 2017)
To feed humanity, while maintaining a stable and diverse biosphere, crop science needs to adapt to an open research environment where genetic resources and the data demonstrating the environments in which they are effective are freely shared. The challenge faced is to expand crop production on a reduced land area, due to environmental degradation caused by human encroachment and climate change, while maintaining biodiversity. Individual researchers are discovering alleles and genetic combinations that are effective in certain environments but not in others. These data and alleles are useful globally to speed progress in breeding for similar environments while not wasting time on ineffective genotypes. However, currently, there are significant barriers to the sharing of genetic resources and their underpinning data, which must be overcome if we are to sustain the planet for future generations.